THE INFLUENCE OF SOCIAL MEDIA IN INCREASING BRAND LOYALTY OF ISLAMIC BANKS WITH BRAND TRUST AS A MEDIATOR AMONG GENERATION Z - Febrianto, Dhea Aulia; Busyro, Wahyi; Jamilah, Putri; Septianingsih, Rika (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to analyze the influence of social media on brand loyalty with brand trust as a mediating variable in Islamic financial institutions. The background of this study is grounded in the increasing intensity of social media use among young people, particularly Generation Z, who have become a potential segment for Islamic banking. The research method used is quantitative with Partial Least Squares–Structural Equation Modeling (PLS-SEM) analysis through the SmartPLS software. A sample of 120 respondents was obtained using purposive sampling. Data were collected through a Likert-scale questionnaire that included indicators of social media, brand trust, and brand loyalty. The results show that social media has a positive effect on brand trust and brand loyalty, and that brand trust is able to mediate the relationship between them significantly. These findings confirm that optimizing social media can be an effective strategy in building customer trust and loyalty, thereby supporting the sustainability of Islamic financial institutions in facing competition in the modern banking industry.